Implementasi Augmented Reality dalam bentuk Location Based Service (LBS) pada hotel di Kota Pekanbaru berbasis Android - Nadya Tri Ayunestina; Sugeng Purwantoro; Yuli Fitrisia (Politeknik Caltex Riau, 2020)
Pekanbaru is the largest cities in Riau province with a very rapid rate of economic growth. This is affecting the business in the hotel sector developing rapidly in the city of Pekanbaru. Augmented Reality (AR) is an innovation that combines virtual and real objects. In this era, people tend to like applications with interactive visual displays. The application of AR technology in the form of LBS on hotels in the city of Pekanbaru based on android is expected to help immigrants or people who need hotel information when visiting the city of Pekanbaru. Users can search for hotels by tracking from the AR camera on the application and knowing the distance and route to get to the hotel. Testing of this application is done by Usability Testing through questionnaires and Blackbox Testing to test functional suitability. Based on the results of the questionnaire found that the application meets the criteria of usability testing where 78,67% of respondents agreed that the application is easy to understand. 71,3% of respondents agreed that the application has an efficient function. 76% of respondents agreed that the appearance of the application is easy to remember. 78,92% of respondents agreed that the application runs well without an error. 72,12% of respondents agreed that the application meets user satisfaction and 82,67% of users would suggest this application as a medium of hotel information in the city of Pekanbaru. Based on the results of Blackbox testing, the application can run smoothly according to existing functional needs.